Consórcios públicos interfederativos em Minas Gerais: arranjos intermunicipais para a gestão regional associada de políticas públicas - César, Paulo Sérgio Mendes (2017)
Most inter-municipal public consortia were created to meet the specific needs of municipal public services. Considering the current fiscal commitment that affects a large part of the municipal public administrations in Brazil, the present work proposes to investigate the phenomenon of the creation of interfederatives public consortia as a potential solution to the difficulties inherent to the implementation and execution of several public policies o Municipal competence. To do so, a priori, it discusses the Brazilian federal system, its main characteristics and values, passing through the theories of decentralization, the distribution of resources and the burden of fiscal federalism to the evolution and framing of the municipality in the current federal pact. Then, in order to better understand the logic of collective action, leaving the bibliography of Mancur Olson and similar, the work investigates the main aspects related to collective action, such as group size, positive and negative selective incentives, coercion mechanisms, among others. Thus, starting from the collective action, one arrives at the interfederative cooperation, studying the existing institutes in our country and its main characteristics. In addition to public consortia, administrative agreements, management contracts and associations of municipalities are investigated. Among these forms, the public consortiums figure in the proper chapter, ranging from the origins of their idealization, to their characteristics, advantages and peculiar constraints of the consortia. Then, entering the universe of public consortia in Minas Gerais and using secondary data from official sites, the work succinctly seeks to demonstrate the profile of the municipalities of Minas Gerais, to reveal the evolution and panorama of the consortia in the state, as well as to point out the occurrence of various aspects from Olson of consortium processes in Minas Gerais. The main incentives for consortiums by government or related entities are still investigated. Aiming to investigate the main motivations for the creation of consortiums of Minas Gerais, as well as to know their structures and perspectives, specific research was carried out, the results of which